It is rocket science – why dietary nitrate is hard to 'beet'! Part I: twists and turns in the realization of the nitrate–nitrite–NO pathway. (6th May 2016) - Khatri, Jibran; Mills, Charlotte Elizabeth; Maskell, Perry; Odongerel, Chimed; Webb, Andrew James
Abstract : Dietary nitrate (found in green leafy vegetables, such as rocket, and in beetroot) is now recognized to be an important source of nitric oxide (NO), via the nitrate–nitrite–NO pathway. Dietary nitrate confers several cardiovascular beneficial effects on blood pressure, platelets, endothelial function, mitochondrial efficiency and exercise. While this pathway may now seem obvious, its realization followed a rather tortuous course over two decades. Early steps included the discovery that nitrite was a source of NO in the ischaemic heart but this appeared to have deleterious effects. In addition, nitrate‐derived nitrite provided a gastric source of NO. However, residual nitrite was not thought to be absorbed systemically. Nitrite was also considered to be physiologically inert but potentially carcinogenic, through N ‐nitrosamine formation. In Part 1 of a two‐part Review on the nitrate‐nitrite‐NO pathway we describe key twists and turns in the elucidation of the pathway and the underlying mechanisms. This provides the critical foundation for the more recent developments in the nitrate–nitrite–NO pathway which are covered in Part 2.